The impact of sukuk on corporate financing: Malaysia evidence - Haron, Razali; Ibrahim, Khairunisah (IIUM Institute of Islamic Banking and Finance, 2012)
A remarkable effect of bond market development on corporate financing is detected among firms in Malaysia en route the study to identify the existence of target capital structure and simultaneously explore firm specific and country specific determinants of target capital structure for firms in Malaysia. This is argued to be the effect of the phenomenal development of sukuk, or Shariah-compliant bonds in Malaysia. The distinctive effect of bond market development with sukuk element on Malaysian firms shows the substantial influence of country specific factors like bond market development as well as governance incorporate financing decision. Employing the dynamic Partial Adjustment Model estimated based on the Generalized Method of Moments (GMM) estimator using data of nonfinancial listed firms for the period of 2000-2009, this study contributes to the existing literature by highlighting the impact ofa well-developed sukuk in bond market development on corporate financing decision and how good governance can ensure liquid and vibrant bond market as an alternative financial intermediary. This study concludes that several factors significantly influence target capital structure and the element of sukuk in bond market in Malaysia coupled with good governance have a substantial impact on corporate financing decision among firms in Malaysia